Alcohol inhibits T-cell glucose metabolism and hepatitis in ALDH2-deficient mice and humans: roles of acetaldehyde and glucocorticoids. Issue 7 (18th August 2018) - Gao, Yanhang; Zhou, Zhou; Ren, Tianyi; Kim, Seung-Jin; He, Yong; Seo, Wonhyo; Guillot, Adrien; Ding, Yanhua; Wu, Ruihong; Shao, Shuang; Wang, Xiaomei; Zhang, Hong; et al.
Abstract : Objective: Aldehyde dehydrogenase 2 (ALDH2), a key enzyme to detoxify acetaldehyde in the liver, exists in both active and inactive forms in humans. Individuals with inactive ALDH2 accumulate acetaldehyde after alcohol consumption. However, how acetaldehyde affects T-cell hepatitis remains unknown. Design: Wild-type (WT) and Aldh2 knockout ( Aldh2 -/- ) mice were subjected to chronic ethanol feeding and concanavalin A (ConA)-induced T-cell hepatitis. Effects of acetaldehyde on T-cell glucose metabolism were investigated in vitro. Human subjects were recruited for binge drinking and plasma cortisol and corticosterone measurement. Results: Ethanol feeding exacerbated ConA-induced hepatitis in WT mice but surprisingly attenuated it in Aldh2 -/- mice despite higher acetaldehyde levels in Aldh2 -/- mice. Elevation of serum cytokines and their downstream signals in the liver post-ConA injection was attenuated in ethanol-fed Aldh2 -/- mice compared to WT mice. In vitro exposure to acetaldehyde inhibited ConA-induced production of several cytokines without affecting their mRNAs in mouse splenocytes. Acetaldehyde also attenuated interferon-γ production in phytohaemagglutinin-stimulated human peripheral lymphocytes. Mechanistically, acetaldehyde interfered with glucose metabolism in T cells by inhibiting aerobic glycolysis-related signal pathways. Finally, compared to WT mice, ethanol-fed Aldh2 -/- mice had higher levels of serum corticosterone, a well-known factor that inhibits aerobic glycolysis. Blockade of corticosterone partially restored ConA-mediated hepatitis in ethanol-fed Aldh2 -/- mice. Acute alcohol drinking elevated plasma cortisol and corticosterone levels in human subjects with higher levels in those with inactive ALDH2 than those with active ALDH2. Conclusions: ALDH2 deficiency is associated with elevated acetaldehyde and glucocorticoids post-alcohol consumption, thereby inhibiting T-cell activation and hepatitis.